Hydrophobic latex powder and preparation method thereof

By modifying the combination of polyvinyl alcohol, polymer emulsion, nano-silica sol and anti-caking agent, hydrophobic latex powder is prepared, which solves the problem of degradation in the performance of traditional latex powder in a water environment, and achieves the improvement of high water resistance and hydrophobic performance and green environmental protection characteristics.

CN119552465APending Publication Date: 2025-03-04ANHUI WANWEI HUSN NEW MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411790513.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional latex powder will absorb water when it encounters water or humid environments, resulting in a degradation of performance and cannot meet the needs of high water resistance and water repellency.

Method used

Hydrophobic latex powder is prepared by spray drying using a combination of modified polyvinyl alcohol, polymer emulsion, nanosilicon sol and anti-caking agent.

Benefits of technology

It significantly improves the hydrophobicity and strength properties of latex powder, meets the requirements of high water resistance and water repellent performance, and meets the green building standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses hydrophobic latex powder, and relates to the technical field of latex powder, the hydrophobic latex powder comprises the following preparation raw materials by weight: 8-12 parts of modified polyvinyl alcohol, 500-600 parts of a polymer emulsion, 3-8 parts of an anti-caking agent, and 1.5-2.5 parts of nano silica sol, the modified polyvinyl alcohol is modified by monomer block copolymerization, and the monomer is any one of maleic acid and vinyl group; the nano silica sol is added into the hydrophobic latex powder, so that the hydrophobic agent not only can enhance the functionality, but also can meet the green building standard and meet the environmental protection requirements of modern buildings and products, and is beneficial to sustainable development, the nano silica sol is directly added into the emulsion from the front end to be uniformly mixed, and the problem of non-uniformity during post-mixing is solved; the hydrophobicity of the latex powder is further improved; according to the hydrophobic latex powder disclosed by the invention, the modified polyvinyl alcohol is used for replacing traditional polyvinyl alcohol, so that the hydrophobicity and the strength performance of a water repellent can be enhanced, the preparation process is simple, and industrialization is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of latex powder, and in particular to a hydrophobic latex powder and a preparation method thereof. Background Art

[0002] With the development of construction, coatings and materials science, latex powder has been widely used due to its excellent performance. However, when traditional latex powder encounters water or humid environment, it often absorbs water and loses its performance. This phenomenon not only affects the strength and stability of the material, but also reduces its reliability in long-term use. At the same time, domestic redispersible latex powder is mainly VAE series, and acrylic acid and tert-butyl vinyl carbonate are also supplied in small quantities. When high water resistance, water repellency, waterproofing and other performance requirements are required for latex powder in grout, decorative mortar, exterior wall plastering, waterproof mortar, etc., the ordinary series of latex powder on the market generally cannot meet the standard requirements.

[0003] The performance of latex powder is lacking, mainly because the emulsion produced and the additives added later cannot provide hydrophobic performance well and additives and solvents harmful to the environment are often used in the preparation process. These problems not only affect the environmental protection characteristics of the product, but also bring difficulties to practical application. In order to meet the growing environmental protection requirements and improve the performance of the product, it is urgent to develop efficient hydrophobic latex powder, by optimizing material formulation and preparation technology, to improve the water resistance and application effect of latex powder. Therefore, the present invention aims to solve the above problems, provide a kind of hydrophobic latex powder and preparation method thereof, to improve the comprehensive use performance of latex powder, and ensure its green environmental protection characteristics.

[0004] Patent document with publication number CN101649096A discloses amphoteric redispersible latex powder, which mentions the use of organosiloxane-modified polyvinyl alcohol solution to produce redispersible latex powder.

[0005] The patent document with publication number CN105086308A discloses a water-resistant redispersible latex powder, which mentions that the redispersible latex powder is produced by using vinyl acetate-ethylene-acrylate copolymer modified emulsion, as well as silicone hydrophobic agent, defoaming agent and emulsion stabilizer.

[0006] Patent document with publication number CN115819808A discloses a water-resistant redispersible latex powder and a preparation method thereof, which mentions that polyvinyl formal grafted with organosiloxane is prepared into a spray liquid with a polyvinyl alcohol aqueous solution and a polymer emulsion, and then spray-dried into a redispersible latex powder.

[0007] Patent document with publication number CN110684307A discloses a water-resistant redispersible latex powder and a preparation method thereof, which mentions that versatile carbonic acid emulsion is mixed with vinyl acetate-ethylene copolymer emulsion or styrene acrylic emulsion, and then mixed with an organosilicon crosslinking agent to produce redispersible latex powder.

[0008] In the above-mentioned prior art patents, the water resistance of latex powder is improved to varying degrees by adding or modifying the emulsion with organic siloxane; however, the decorative mortar, grout, waterproof mortar, etc. demanded by the current domestic market have high requirements on hydrophobicity and water absorption, and there is still a great shortage of latex powder products with high cohesive strength, low environmental pollution in the production process, strong hydrophobicity and low water absorption. Summary of the invention

[0009] The object of the present invention is to provide a hydrophobic latex powder and a preparation method thereof, to solve the following technical problems:

[0010] How to improve the hydrophobicity and strength of latex powder.

[0011] The purpose of the present invention can be achieved by the following technical solutions:

[0012] In a first aspect, the present invention discloses a hydrophobic latex powder, comprising the following raw materials in parts by weight: 8-12 parts of modified polyvinyl alcohol, 500-600 parts of polymer latex, 3-8 parts of anti-caking agent, and 1.5-2.5 parts of nano-silica sol.

[0013] Preferably, the hydrophobic latex powder comprises the following raw materials in parts by weight: 10 parts of modified polyvinyl alcohol, 550 parts of polymer latex, 5 parts of anti-caking agent, and 2 parts of nano-silica sol.

[0014] Preferably, the modified polyvinyl alcohol is modified by monomer block copolymerization.

[0015] Preferably, the monomer is any one of maleic acid and vinyl group.

[0016] In the present invention, the modified polyvinyl alcohol is preferably the modified polyvinyl alcohol modified by ethylene block copolymerization produced by Kuraray.

[0017] Preferably, the degree of polymerization of the modified polyvinyl alcohol is 500-2500, and the degree of alcoholysis is 80%-95%.

[0018] More preferably, the degree of polymerization of the modified polyvinyl alcohol is 1800 and the degree of alcoholysis is 90%.

[0019] Preferably, the polymer emulsion is any one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer, acrylic emulsion, or a mixture of any two to three of them in an equal weight ratio.

[0020] Preferably, the polymer emulsion has a solid content of 40%-60% and a Brookfield viscosity of 400-3000 mmpa·s.

[0021] In the present invention, the polymer emulsion is more preferably a mixture of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer, and acrylic emulsion in a ratio of 1:1:1, with a solid content of 50% and a viscosity of 2000 mmpa·s.

[0022] Preferably, the anti-caking agent is a mixture of mineral raw materials and fumed silica in a mass ratio of 1:(0.1-0.5).

[0023] Preferably, the mineral raw material is any one of calcium carbonate, diatomaceous earth, kaolin, talc, and dolomite, or a mixture of any two of them in equal mass ratio.

[0024] More preferably, the mineral raw material is a mixture of calcium carbonate and kaolin in a mass ratio of 1:1.

[0025] In the present invention, the anti-caking agent is more preferably a mixture of calcium carbonate, kaolin and fumed silica in a ratio of 5:5:2.

[0026] In a second aspect, the present invention further discloses a method for preparing the hydrophobic latex powder as described above, comprising the following steps:

[0027] S1, adding modified polyvinyl alcohol into water to swell, passing water vapor and stirring to fully dissolve the polyvinyl alcohol, and obtaining a modified polyvinyl alcohol aqueous solution;

[0028] S2, mixing the modified polyvinyl alcohol aqueous solution with the polymer emulsion and the nano-silica sol, and stirring them evenly to obtain a spray liquid;

[0029] S3, heating the spray liquid online, controlling the temperature at 40-60° C., entering the atomizer, controlling the drying temperature at 130-150° C., spray drying, and uniformly mixing the obtained powder with the anti-caking agent to obtain the hydrophobic latex powder.

[0030] Preferably, the solid content of the polyvinyl alcohol aqueous solution is 8%-25%;

[0031] More preferably, the solid content of the polyvinyl alcohol aqueous solution is 15%.

[0032] Beneficial effects of the present invention:

[0033] 1. Nano-silica sol is added to the hydrophobic latex powder of the present invention, so that the hydrophobic agent can not only enhance functionality, but also meet green building standards, comply with environmental protection requirements of modern buildings and products, and contribute to sustainable development.

[0034] 2. The nano-silica sol in the hydrophobic latex powder of the present invention is directly added into the emulsion from the front end and mixed evenly, which solves the problem of uneven mixing at the end and further improves the hydrophobicity of the latex powder.

[0035] 3. The modified polyvinyl alcohol is used in the hydrophobic latex powder of the present invention to replace the traditional polyvinyl alcohol, which can enhance the hydrophobicity and strength properties of the hydrophobic agent.

[0036] 4. The preparation process of the hydrophobic latex powder of the present invention is simple and can be easily industrialized.

[0037] 5. Compared with conventional water-repellent agents, the water-repellent latex powder of the present invention is a new type of green water-repellent agent, which is green, environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The experimental methods in the following examples are conventional methods unless otherwise specified, and are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified. For example, the polymer emulsion and polyvinyl alcohol used are all products of Wanwei High-Tech; modified polyvinyl alcohol is a product of Japan Kuraray Co., Ltd.; and nano-silica sol is a product of Huihe Yongsheng Nano Technology Co., Ltd.

[0040] Example 1

[0041] Step 1: Prepare the ingredients

[0042] Modified polyvinyl alcohol, polymer emulsion, anti-caking agent and nano-silica sol are prepared according to a weight ratio of 10:550:5:2; wherein the specific types and sources of various substances are as follows:

[0043] Modified polyvinyl alcohol: Use ethylene-modified PVA0488;

[0044] Polymer emulsion: vinyl acetate-ethylene emulsion (viscosity 2210 mPa·s, solid content 49.8%), vinyl acetate-versatate-ethylene emulsion (viscosity 1640 mPa·s, solid content 48.2%), and acrylic emulsion (viscosity 1740 mPa·s, solid content 51.4%) were mixed in a mass ratio of 1:1:1 to obtain a mixture as a polymer emulsion (viscosity 2000 mmPa·s, solid content 50%);

[0045] Anti-caking agent: a mixture of calcium carbonate and kaolin in a mass ratio of 1:1, and then mixed with fumed silica in a mass ratio of 5:1;

[0046] Nano-silica sol: a product produced by Huihe Yongsheng Nano Technology Co., Ltd.

[0047] Step 2: Preparation of hydrophobic latex powder

[0048] (1) Add a small amount of water to a dissolving kettle, add PVA0488, make the water submerge PVA0488, swell for 30 minutes, pass water vapor into the dissolving kettle, raise the temperature to 90°C and continue stirring for 1 hour to fully dissolve PVA0488, and obtain a modified polyvinyl alcohol aqueous solution with a solid content of 15%;

[0049] (2) mixing the modified polyvinyl alcohol aqueous solution, the polymer emulsion and the nano-silica sol and stirring them uniformly to obtain a spray liquid with a viscosity of 525 mPa.s;

[0050] (3) The spray liquid is heated online and the temperature is controlled at 50° C., and then enters an atomizer for spray drying. The inlet temperature of the drying tower is 145° C., and the outlet temperature is 85° C. The obtained powder is mixed with an anti-caking agent and mixed evenly to obtain a hydrophobic latex powder.

[0051] Example 2

[0052] Compared with Example 1, the only difference is that in step 1, modified polyvinyl alcohol, polymer emulsion, anti-caking agent and nano-silica sol are prepared according to a weight ratio of 8:500:3:1.5, and other conditions are exactly the same as the steps, and finally a hydrophobic latex powder is obtained.

[0053] Example 3

[0054] Compared with Example 1, the only difference is that in step 1, modified polyvinyl alcohol, polymer emulsion, anti-caking agent and nano-silica sol are prepared according to a weight ratio of 12:600:8:2.5, and other conditions are exactly the same as the steps, and finally a hydrophobic latex powder is obtained.

[0055] Example 4

[0056] Compared with Example 1, the only difference is that the polymer emulsion is replaced by a mixture of vinyl acetate-ethylene emulsion (viscosity 2210 MPa·s, solid content 49.8%) and vinyl acetate-versatate-ethylene emulsion (viscosity 1640 MPa·s, solid content 49%) in a mass ratio of 1:1 (viscosity 1940 MPa·s, solid content 48.9%); the other steps and conditions are exactly the same, and finally a hydrophobic latex powder is obtained.

[0057] Example 5

[0058] Compared with Example 1, the only difference is that the anti-caking agent is replaced by a mixture of diatomaceous earth, talc and fumed silica in a ratio of 5:5:2; the other steps and conditions are exactly the same, and finally a hydrophobic latex powder is obtained.

[0059] Comparative Example 1

[0060] Compared with Example 1, the only difference is that the modified polyvinyl alcohol is replaced by polyvinyl alcohol, and the other conditions and steps are exactly the same, and finally the hydrophobic latex powder is obtained.

[0061] Comparative Example 2

[0062] Compared with Example 1, the only difference is that the nano-silica sol in step (3) of step 2 is transferred to step (4) and added together with the binder. The other conditions are exactly the same as the steps, and finally a hydrophobic latex powder is obtained.

[0063] Comparative Example 3

[0064] Compared with Example 1, the only difference is that in step (3) of step 2, no nano-silica sol is added, and the other conditions are exactly the same as those of the steps, and finally a hydrophobic latex powder is obtained.

[0065] The hydrophobic latex powders prepared in Examples 1-5 and Comparative Examples 1-3 were tested for performance, and the testing method was as follows:

[0066] Hydrophobicity: refer to GB / T29594-2013;

[0067] Strength properties: Refer to JCT 1004-2006.

[0068] The test results are listed in Table 1. Table 1 is as follows:

[0069] Table 1

[0070] 30min water absorption (g) 240min water absorption (g) Flexural strength(MPa) Compressive strength(MPa) Example 1 1.65 4.68 4.85 15.89 Example 2 1.73 4.75 4.52 15.68 Example 3 1.74 4.79 4.45 15.44 Example 4 1.69 4.69 4.55 15.65 Example 5 1.70 4.74 4.56 15.74 Comparative Example 1 2.56 6.23 2.56 13.25 Comparative Example 2 2.98 6.45 2.69 12.65 Comparative Example 3 2.45 6.12 2.11 11.56

[0071] By analyzing the data in Table 1, it can be found that compared with Comparative Examples 1-2, the hydrophobic latex powder prepared in Examples 1-5 absorbs less water at 30min and 240min, indicating that it has better hydrophobicity. At the same time, its flexural strength and compressive strength are higher, indicating that it has stronger mechanical properties.

[0072] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A hydrophobic latex powder, characterized in that: The preparation method comprises the following raw materials in parts by weight: 8-12 parts of modified polyvinyl alcohol, 500-600 parts of polymer emulsion, 3-8 parts of anti-caking agent and 1.5-2.5 parts of nano silica sol.

2. The hydrophobic latex powder according to claim 1, characterized in that: The modified polyvinyl alcohol is modified by monomer block copolymerization.

3. The hydrophobic latex powder according to claim 2, characterized in that: The monomer is any one of maleic acid and vinyl group.

4. The hydrophobic latex powder according to claim 2, characterized in that: The modified polyvinyl alcohol has a polymerization degree of 500-2500 and an alcoholysis degree of 80%-95%.

5. The hydrophobic latex powder according to claim 1, characterized in that: The polymer emulsion is any one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic emulsion, or a mixture of any two to three of them in equal weight ratio.

6. The method for preparing the hydrophobic latex powder according to claim 5, characterized in that: The solid content of the polymer emulsion is 40%-60%, and the Brookfield viscosity is 400-3000 mmpa·s.

7. The hydrophobic latex powder according to claim 1, characterized in that: The anti-caking agent is a mixture of mineral raw materials and fumed silicon dioxide in a mass ratio of 1:(0.1-0.5).

8. The hydrophobic latex powder according to claim 7, characterized in that: The mineral raw material is any one of calcium carbonate, diatomaceous earth, kaolin, talcum powder and dolomite, or a mixture of any two of them in equal mass ratio.

9. The hydrophobic latex powder according to claim 1, characterized in that: The mineral raw material is a mixture of calcium carbonate and kaolin in a mass ratio of 1:

1.

10. A method for preparing a hydrophobic latex powder according to any one of claims 1 to 9, characterized in that: The steps include: S1, adding modified polyvinyl alcohol into water to swell, passing water vapor and stirring to fully dissolve the polyvinyl alcohol, and obtaining a modified polyvinyl alcohol aqueous solution; S2, mixing the modified polyvinyl alcohol aqueous solution with the polymer emulsion and the nano-silica sol, and stirring them evenly to obtain a spray liquid; S3, heating the spray liquid online, controlling the temperature at 40-60° C., entering the atomizer, controlling the drying temperature at 130-150° C., spray drying, and uniformly mixing the obtained powder with the anti-caking agent to obtain the hydrophobic latex powder.

11. The hydrophobic latex powder according to claim 10, characterized in that: The solid content of the polyvinyl alcohol aqueous solution is 8%-25%.

Citation Information

Patent Citations

  • Ampholytic re-dispersible emulsion powder

    CN101649096A

  • Water-resistant re-dispersible latex powder

    CN105086308A

  • Water-resistant redispersible latex powder and preparation method thereof

    CN110684307A

  • Water-resistant redispersible latex powder and preparation method thereof

    CN115819808A